Managing organizational PR activities in crisis situations - Viazova, Ryta; Volkova, Valeriya; Yudina, Olga (Management and Entrepreneurship: Trends of Development, 2023)
Public relations have proved to be an efficient apparatus in the organizational crisis management, acting to resolve crisis situations, promoting organizations/enterprises, their products or services by shaping public opinions and coordinating with civil society. PR activities involve a set of different practices, including managing the company’s image, media mediation, organizing various events, corporate communications, which are aimed at mutually beneficial relationships between staff and customers, partners, and other publics. Therefore, the relevance of our research is determined by the need to increase the effectiveness of PR activities in crisis situations at domestic enterprises in order to provide their development and successful functioning as well as avoid the threats to organizational reputation and image caused by crisis situations. The study is aimed at analyzing the theoretical and practical aspects of managing enterprises’ PR activities in crisis situations and revealing the role of effective strategies and methods in anti-crisis PR as a means of preserving the enterprise’s image. The subject matter of this paper is organizational PR anti-crisis activities. In the article, critical analysis, synthesis and comparison were applied as the basic research principles. The results suggest that managing the organizational PR activities in crisis situations is successful if the following measures are implemented, namely analysis of the company’s (organization) image by studying the publics’ opinions; development of a crisis response strategy together with the management; implementation of PR programs through establishing communications with general public and target audiences. It is determined that in crisis situations, the main task is to manage the communication process aimed at spreading the organization’s viewpoint, influencing the problem perception, preventing the spread of rumors and disinformation as well as neutralizing or minimizing the consequences of the crisis for the image and reputation of the organization. JEL Classification: М 10, M14, M15, M19